USE OF MINIMALLY INVASIVE TECHNOLOGIES IN THE TREATMENT OF THE MUSCULOSKELETAL SYSTEM IN PATIENTS WITH POLYTRAUMA - Temurov A.A., Ziyotov L.I. (Central Asian Journal of Medicine, 2025)
The separation of polytrauma into a separate category is associated with the severity of the injuries, which should be taken into account when providing medical care. The combination of injuries to the chest, abdomen, and musculoskeletal system is of particular interest. These combinations of traumatic injuries are accompanied not only by traumatic shock, but also by the development of hemorrhagic and peritoneal syndromes. At the same time, damage to the musculoskeletal system complicates the diagnosis and treatment of victims with damage to the internal organs of the thoracic and abdominal cavities, is a prerequisite for many life-threatening complications (shock, fatty embolism, respiratory distress syndrome, pneumonia) in the 1st and 2nd periods of traumatic diseases. One of the most severe and frequent injuries of the musculoskeletal system is bone fractures, which occur in 90-98% of patients with multiple injuries and in 62.0-78.9% of patients with combined injuries. Mortality among victims of polytrauma varies from 3.8 to 45.3%, and the disability rate reaches from 10.3% to 43.4%.